2015
DOI: 10.13057/psnmbi/m010430
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan performans pedet sapi Peranakan Ongole pasca sapih melalui perbaikan manajemen dengan pemanfaatan sumberdaya lokal

Abstract: Abstrak. Utomo B, Oelviani R, Subiharta. 2015. Peningkatan performa pedet sapi Peranakan Ongole pascasapih melalui perbaikan manajemen dengan pemanfaatan sumber daya lokal. Pros Sem Nas Masy Biodiv Indon 1: [838][839][840][841][842]. Salah satu sapi lokal yang potensial untuk dikembangkan sebagai penghasil daging adalah sapi Peranakan Ongole (PO), mengingat sapi tersebut populasinya cukup tinggi dan menyebar hampir di seluruh daerah di Indonesia. Kebumen merupakan salah satu sentra peternakan sapi potong lokal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Ongole grade cattle is the result of an uncontrolled mating and a grading up of Java and Sumba Ongole cattle (Suyadi et al, 2014, Hardosubroto, 1994. In Kebumen, Central Java, PO cattle genetic improvement program have been done before 1930s (Utomo et al, 2015). Kebumen also become as one of the breeding center of PO cattle (DGLSAH, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ongole grade cattle is the result of an uncontrolled mating and a grading up of Java and Sumba Ongole cattle (Suyadi et al, 2014, Hardosubroto, 1994. In Kebumen, Central Java, PO cattle genetic improvement program have been done before 1930s (Utomo et al, 2015). Kebumen also become as one of the breeding center of PO cattle (DGLSAH, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Kebumen, breeding programe to improve genetic quality of PO cattle had been done before 1930 and they look like a pure Ongole cattle (Utomo et al, 2015). Based on physical observation in the field, we found the similarities between Kebumen Ongole grade cattle and Brahman cattle.…”
Section: Introductionmentioning
confidence: 77%
“…So then, almost about 90% of the Ongole Grade cattle population in Indonesia were on Java Island. Previous researchers reported that in Kebumen (Central Java), long before the Ongolisation program in the 1930s, efforts had been made to genetically improve zebu cattle originating from Madras (East India) and have continued to grow, so that recently Ongole Grade cattle in Kebumen were also called as Madras cattle and reported had quality like pure Ongole cattle (Utomo et al 2015).…”
Section: Introductionmentioning
confidence: 99%